2013
DOI: 10.1155/2013/687317
|View full text |Cite
|
Sign up to set email alerts
|

Variance and Passivity Constrained Fuzzy Control for Nonlinear Ship Steering Systems with State Multiplicative Noises

Abstract: The variance and passivity constrained fuzzy control problem for the nonlinear ship steering systems with state multiplicative noises is investigated. The continuous-time Takagi-Sugeno fuzzy model is used to represent the nonlinear ship steering systems with state multiplicative noises. In order to simultaneously achieve variance, passivity, and stability performances, some sufficient conditions are derived based on the Lyapunov theory. Employing the matrix transformation technique, these sufficient conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Additionally, it can be observed that the proposed controller is more effective since the response time is as small as below 0.2 seconds for position and heading, and 0.5 seconds for velocities. Based on the simulation results, the proposed controller performs better compared to that given in [25,27] and [35], by having small response time of less than 0.5 seconds. Fig.…”
Section: Simulation and Analysismentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, it can be observed that the proposed controller is more effective since the response time is as small as below 0.2 seconds for position and heading, and 0.5 seconds for velocities. Based on the simulation results, the proposed controller performs better compared to that given in [25,27] and [35], by having small response time of less than 0.5 seconds. Fig.…”
Section: Simulation and Analysismentioning
confidence: 95%
“…The purpose of the study given in [29] was to achieve the H ∞ performance constraints and cope with the nastiest case effects of the disturbances. More works related to robust fuzzy have been given in [27][28][29][30][31][32][33][34][35][37][38]. Some of these literatures have no direct comparison to the proposed work but show the richness of fuzzy control designs.…”
Section: Introductionmentioning
confidence: 99%
“…The above attractive features make passivity an important tool to analyse and synthesise stable control systems. According to individual state variance constraint and passivity constraint, a multi‐objective fuzzy control approach has been investigated in [35, 36]. However, the advantage of the sliding mode control was not adopted in [35, 36].…”
Section: Introductionmentioning
confidence: 99%
“…According to individual state variance constraint and passivity constraint, a multi‐objective fuzzy control approach has been investigated in [35, 36]. However, the advantage of the sliding mode control was not adopted in [35, 36]. Extending the results of [35, 36], the motivation of this paper is to combine sliding mode control, covariance control, passivity‐based control and fuzzy control to develop a novel multi‐objective control scheme for the discrete‐time non‐linear stochastic systems.…”
Section: Introductionmentioning
confidence: 99%
“…An important fact is that the design problem is a standard feasibility problem with several LMIs. According to the T-S fuzzy model with multiplicative noise, there exist only few approaches investigated to solve the abovementioned problems of control design and stability analysis for continuous-time [23,24], as well as for discrete-time TS models [25][26][27] and these papers only present some results on stability analysis, mean-square stabilization, and control for TS fuzzy stochastic systems with multiplicative noises.…”
Section: Introductionmentioning
confidence: 99%